Nationwide mortality trends of delirium in Australia and the United States from 2006 to 2016. (9th March 2021) - Wu, Harry; Mach, John; Le Couteur, David G.; Hilmer, Sarah N.
Abstract: Objectives: To examine nationwide trends in delirium mortality in Australia and the United States between 2006 and 2016. Methods: Delirium mortality data for Australian and United States populations were obtained from World Health Organization Mortality Database. Mortality trends were assessed using joinpoint regression. Results: Age‐adjusted delirium mortality increased by 16.35%/year and 4.04%/year in Australia and the United States, respectively. Average annual age‐adjusted delirium mortality rate (per 1 000 000 population) was 2.90 in Australia, and 1.06 in the United States. Death rates from delirium increased with age. Mortality was consistently higher in men than women, but the rate of annual increase was greater in women. Conclusions: Our study provided important population‐level data on delirium and its outcomes in Australia and the United States. Reported death rates attributed to delirium increased over the 11‐year period in both countries and were consistently higher in Australia than the United States. There were distinct age and sex differences in mortality trends.